Relationships of isometric mid-thigh pull variables to weightlifting performance - Beckham, G.; Mizuguchi, S.; Carter, C.; Sato, K.; Ramsey, M.; Lamont, H.; Hornsby, G.; Haff, G.; Stone, M. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The purpose of this study was to evaluate the relationship between weightlifting performance (snatch, clean and jerk, and total) and variables obtained from the isometric mid-thigh pull (IMTP). Methods: Twelve weightlifters, ranging from novice to advanced, performed the IMTP 10 days after a competition. Correlations were used to evaluate relationships between variables of the IMTP and absolute and scaled competition results. Results: Unscaled competition results correlated strongly with IRFD (0-200ms: r=0.567-0.645, 0-250ms: r=0.722-0.781) while results correlated weakly with Peak IRFD (5ms window, r=0.360-0.426). Absolute peak force values correlated very strongly with absolute values for the competition performance (r=0.830-0.838). Force at 100ms, 150ms, 200ms and 250ms also correlated strongly with competition results (r=0.643-0.647, r=0.605-0.636, r=0.714-0.732, r=0.801-0.804). Similar findings were noted for allometrically scaled values. Conclusion: Measures of average IRFD probably represent a more relevant variable to dynamic performance than does Peak IRFD (5ms). Maximum isometric strength also is likely to have a strong role in weightlifting performance.